(untitled) (Baghdad Science Journal, 2020)
In the present work, the surface properties of mixed binary surfactants containing sodium dodecylbenzene sulfate (SDBS) and Tween 80 (TW80) surfactants in aqueous solutions were studied at temperature 293 K using surface tension measurements. The critical micelle concentration (cmc) magnitude for both individual surfactants and their mixtures were established the obtained results revealed that the magnitude of cmc of the mixtures are less than the magnitude of individual surfactants and decrease with the increase in Tween 80 percent in solution which indicate the nonideal mixing of the two surfactants. The values of molecular interaction parameters and the mole fraction of surfactants in the micelle (X1) were calculated on the basis of Rubingh’s model and showed that the interaction parameter is always negative but at 0.9 mole fraction of TW80 surfactant (α1) is positive